High density galaxy environments — the radio view. Issue Volume 15:Issue S359(2020) (March 2019) - Hardcastle, Martin J.
Abstract: Radio-loud active galaxies are widely believed to have a strong impact on their environments, and often lie in groups and clusters of galaxies. In this article I summarize what we can understand about the sources' effects on their surroundings from the perspective of radio galaxy physics, with special reference to the energetics of the impact on the external medium and its inference from large statistical studies of radio galaxies.